CARACTERIZAÇÃO MORFOLÓGICA E MOLECULAR DA COMUNIDADE DE CIANOBACTÉRIAS EM UMA LAGUNA COSTEIRA EUTROFIZADA - BRITO, Milena Viana (2020)
The urbanized Jansen lagoon has resulted after the damming of a mangrove area on the Brazilian Amazon coast. The influence of abiotic factors on the diversity and occurrence of toxigenic blooms of cyanobacteria were evaluated, as well as the morpho-molecular characterization of potentially toxic cyanobacteria isolates was also performed. Samples were collected at five points in the lagoon during 2018 and 2019 to represent different rainfall regimes. For the phytoplankton analysis, 39 species of cyanobacteria were identified, with 11 genera of possibly toxic cyanobacteria. All samples were inoculated in ASM-1, BG-11, and BG-11N (without nitrogen). After the incubation period, the potentially toxic strains were selected based on morphology and a total of seven unicyanobacterial cultures belonging to the genera Anabaena, Anagnostidinema, Microcystis, Oscillatoria, and Westiellopsis were obtained. Potentially toxigenic strains were identified by 16S rRNA gene sequencing and tested for the presence of genes involved in the biosynthetic pathways five toxins (anatoxin, cylindrospermopsin, nodularin, microcystin, and saxitoxin). The physical and chemical characteristics reported during this study revealed aspects of a highly eutrophic environment, with an excess of nitrogen compounds, mainly ammonia, which may have favored the higher occurrence of blooms and toxic species. The main predictive environmental variables, selected using the multiple linear regression model (GLM) and dispersion graphs, showed an increase in water temperature and salinity to explain the variation in the abundance of the operational taxonomic units (OTUs). The distribution of OTUs 1 (Nostocales) and 2 (Chroococcales) correlated with these main variables, and the distribution of OTU 3 (Oscillatoriales) had a higher correlation with the higher concentrations of total nitrogen. That is the first description of the occurrence of the genus Westiellopsis in this region, with the confirmation of the mcyA and mcyE genes related to microcystin production by DNA sequencing. This study reported the presence of toxigenic strains of cyanobacteria, indicating the need for continuous monitoring, because the riverside population uses this lagoon as a subsistence fishing site.